PENINGKATAN KECERDASAN DAN KREATIVITAS SISWA (Improving Students’ Intelligence and Creativity) PENINGKATAN KECERDASAN DAN KREATIVITAS SISWA (Improving Students’ Intelligence and Creativity) - Saparahayuningsih, Sri (Universitas Negeri Semarang, 2010)
Improving students’ intelligence and creativity is very important for our country’s development. It will be formed when educational process gives students opportunity to think convergently and divergently. So far, improving students’ intelligence and creativity has not been done satisfactorily. As a result, students’ intelligence and creativity cannot develop optimally. This writing offers the psycologists to optimize their activities so that students’ intelligence and creativity will be able to develop optimally. Teachers who can optimize students’ intelligence and creativity will be able to deliver students who can stand alone in the future. They will be positive value for their country. Keywords: intelligence, creativity, and education.